Electron–hole collisions in an atomically thin semiconductor. (May 2019) - Langer, F; Schmid, C P; Schlauderer, S; Nagler, P; Schüller, C; Korn, T; Gmitra, M; Fabian, J; Hawkins, P G; Huttner, U; Steiner, J T; Koch, S W; et al.
Abstract: Strong-field biasing of a solid with intense lightwaves leads to simultaneous interband excitation and intraband acceleration of electron–hole pairs. These coupled dynamics result in high-harmonic emission from the bulk solid. For a controlled acceleration of quasiparticles with well-defined initial conditions, we prepare coherent electron–hole pairs by a resonant near - infrared pulse before a strong multi-terahertz field accelerates these entities. The ballistic dynamics manifests itself as high-order sidebands to the near-infrared excitation spectrum. This mechanism allows for the implementation of a quasiparticle collider in order to study those entities in close analogy to conventional collision experiments. Accelerating electrons and holes in a monolayer of a transition metal dichalcogenide extends this scheme to internal quantum degrees of freedom. We show how a strong lightwave can transport electron–hole pairs from one valley to the other faster than one oscillation of the carrier wave, effectively switching the valley pseudospin on a sub-cycle scale. This scheme paves the way to ultimately fast valleytronics.